Temporal Relationships Between Abdominal Pain, Psychological Distress and Coping in Patients With IBS – A Time Series Approach - Engel, Felicitas; Stadnitski, Tatjana; Stroe-Kunold, Esther; Berens, Sabrina; Schäfert, Rainer; Wild, Beate (Frontiers in Psychiatry, 2022)
Abstract Objective: Irritable bowel syndrome (IBS) is a chronic disease leading to abdominal pain that is often related to psychological distress. The aim of the study was to investigate the temporal relationships between abdominal pain and psychological variables in patients with IBS. Methods: This longitudinal diary study included eight patients from a waiting group, recruited in the frame of a pilot intervention study. During their waiting time of three months the patients answered questions daily regarding somatic and psychological variables using an online diary. All patients were considered and analyzed as single cases. The temporal dynamics between the time series of psycho-somatic variables were analyzed using a vector autoregressive (VAR) modeling approach. Results: For all patients, positive same-day correlations between somatic and psychological time series were observed. The highest same-day correlations were found between somatic symptoms and pain-related discomfort (r=0.40 to r= 0.94). Altogether, n=26 significant lagged relationships were identified; n=17 (65%) indicated that somatic values were predictive of psychological complaints on the following days. N=9 (35%) lagged relationships indicated an opposite relationship in that psychological complaints were predictive of somatic symptoms. Three patients showed a significant positive same-day correlation between abdominal pain and use of a positive coping strategy. However, significant lagged relationships in two patients showed that for these patients the use of positive thinking as a coping strategy was unhelpful in reducing pain on the following days. Conclusions: In patients with IBS abdominal symptoms appear to be closely related to psychological symptoms. For some patients, somatic complaints predict psychological complaints, in other patients the directionality is opposite. The impact of coping strategies on somatic symptoms varies among patients, therefore their role for a possible reduction of pain should be further explored. The results suggest the need of characterizing patients individually for effective health interventions. Individual time series analyses provide helpful tools for finding reasonable person-level moderators.